The landscape of the monastic endeavour: The choices of St Sava of Serbia - Popović Danica (Balcanica)
This paper approaches the question of the selection of site intended for monastic ascetic pursuits taking the example of St Sava of Serbia. Sava’s choices were based on his masterful knowledge of Byzantine eremitic tradition and his own substantial monastic experience. This is evidenced by the hesychasteria he founded: he gave physical form to the concept of locus amoenus in the Karyes kellion of the monastery of Hilandar, while the concept of locus horridus was embodied in the cave hermitages of the monasteries of Studenica and Mileševa. The methodological framework of this research is informed by current landscape studies.